Drugs of abuse, cytostatic drugs and iodinated contrast media in tap water from the Madrid region (central Spain):A case study to analyse their occurrence and human health risk characterization. (January 2016) - Mendoza, A.; Zonja, B.; Mastroianni, N.; Negreira, N.; López de Alda, M.; Pérez, S.; Barceló, D.; Gil, A.; Valcárcel, Y.
Abstract: This work analyses the presence of forty-eight emerging pollutants, including twenty-five drugs of abuse and metabolites, seventeen cytostatic drugs and six iodinated contrast media, in tap water from the Madrid Region. Analysis of the target compounds in the tap water was performed by means of (on-line or off-line) solid-phase extraction followed by analysis by liquid chromatography–tandem mass spectrometry. A preliminary human health risk characterization was undertaken for each individual compound and for different groups of compounds with a common mechanism of action found in tap water. The results of the study showed the presence of eight out of the twenty-five drugs of abuse and metabolites analysed, namely, the cocainics cocaine and benzoylecgonine, the amphetamine-type stimulants ephedrine, 3, 4-methylenedioxymethamphetamine and methamphetamine, the opioid methadone and its metabolite 2-ethylene-1, 5-dimethyl-3, 3-diphenylpyrrolidine and, finally caffeine at concentrations ranging from 0.11 to 502 ng L − 1 . Four out of the six analysed iodinated contrast media, namely, diatrizoate, iohexol, iomeprol and iopromide, were detected in at least one sample, with concentration values varying between 0.4 and 5 ng L − 1 . Cytostatic compounds were not detected in any sample. Caffeine was the substance showing the highest concentrations, up to 502 ng L − 1, mainly in the drinking water sampling point located in Madrid city. Among the other drugs of abuse, the most abundant compounds were cocaine and benzoylecgonine, detected at concentrations ranging from 0.11 to 86 ng L − 1 and from 0.11 to 53 ng L − 1, respectively. Regarding iodinated contrast media, iohexol was the most ubiquitous and abundant compound, with a frequency of detection of 100% and concentrations from 0.5 to 5.0 ng L − 1 in basically the same range in all sampling points. Taking into account the results and types of treatment applied, ozonisation plus granular activated carbon filtration appears to be efficient in the removal of cocaine and benzoylecgonine. For the amphetamine-type stimulants, opioids and caffeine, ozonisation plus granular activated carbon filtration and ultrafiltration plus reverse osmosis showed higher removal efficiency than sand filtration. The human health risk characterization performed indicates that the lifetime consumption of the tap waters analysed has associated a negligible human health concern. Highlights: Drugs of abuse and iodinated contrast media were found in the tap water from Madrid. Cytostatic drugs were not detected in this matrix. The highest concentrations corresponded to caffeine, followed by cocainics. No potential human health concern due to lifetime consumption of this water